The soil geochemistry of the area between Cansizhimik, Galusagi and Topalkem (Baskil-ELAZIG) villages - Türkyilmaz, Bayrm; Şaşmaz, Ahmet (My University, 1999)
This research was carried out as geochemical soil survey to the south of Baskil town and on the area of 6.5 sq.km. of Baskil Magmatites. -80 mesh fraction of soil samples were analyzed for Cu, Pb, Zn and As and the results of the analysis were evaluted statistically in order to determine background, threshold and anomaly values of each metal. Anomaly areas are compared with the geology of investigation area. According to this comparison, Pb-Zn anomalies are similar with each other and they all coincide with fracture, fault and contact zones. Although Cu and As anomalies are similar to Pb-Zn anomalies at the eastern part, they have different characteristics at the northwestern part of the area. Cu and As anomalies are more or less regular and tend to extend towards the northwest part. Therefore these anomalies may reflect a mineralization to the further northwest of investigation area.
Cansizhimik, Galusagi ve Topalkem (Baskil-ELAZIG) koyleri arasindaki alanin toprak jeokimyasi
Keywords: Baskil magmatites; Soil geochemistry